"Unboxing the sandbox": a new method of learning PHP advanced web programming / Mohamad Rahimi Mohamad Rosman, Mohammad Azhan Abdul Aziz and Mohd Akmal Faiz Osman - Mohamad Rosman, Mohamad Rahimi; Abdul Aziz, Mohammad Azhan; Osman, Mohd Akmal Faiz (Universiti Teknologi MARA Cawangan Kelantan, 2018)
The growth of the Internet marks the necessities of a better web application. In Malaysia, the Internet penetration stands at 77.6% of the total population (Malaysian Communications and Multimedia Commission, 2017). Thus, the demand for information system programmer and web programmer has significantly increased over the years. One of the popular programming languages is PHP: Hypertext Preprocessor (Verma, 2017). However, many students especially those newbies are having a problem to effectively mastering and proficient in this language. Therefore, this study is intended to improve students’ performance and understanding towards PHP programming language. In doing so, we introduce a new educational tool called “MyPHP SandBox”. The sandbox was developed in two (2) phases. First, an empirical study was conducted. A total of five (5) respondents selected from the Faculty of Information Management, Universiti Teknologi MARA Kelantan. Then, based on the empirical findings, the information and content of the sandbox are tailored to the needs of the learners. In term of usefulness, the sandbox can be used as a diagnostic tool for continuous improvement of student performance. The system helps educators to monitor learners progress and make any recommendation as needed. From an empirical viewpoint, findings may help educators to improve their teaching delivery by focusing on specific criteria that contribute to effective learning experience among learners. Furthermore, the product can be commercialized as an eBook, App, Print Publication and Paid Online Learning Content